Uzbekistan’s initiatives to ensure peace and stability in Central Asia, raising relations of friendship and cooperation with neighboring states to a new level - Tashev Qahramon Ozodbekovich (Dynamics of Politics and Democracy, 2025)
Purpose: This study aims to analyze Uzbekistan’s proactive foreign policy initiatives to ensure peace, stability, and deeper regional integration in Central Asia, particularly through diplomacy, environmental action, infrastructure development, and cross-border cooperation. Research methodology: The research applies a qualitative analysis approach, drawing from official documents, international agreements, and speeches by Uzbekistan’s leadership. The analysis focuses on five thematic areas: peace-building in Afghanistan, ecological cooperation, water management, transport infrastructure, and nuclear disarmament. Results: Uzbekistan has emerged as a regional leader by facilitating consultative meetings among Central Asian heads of state, advocating for a nuclear-weapon-free zone, investing in sustainable transport networks like the China-Kyrgyzstan-Uzbekistan railway, and promoting ecological innovation in the Aral Sea basin. These initiatives have enhanced economic ties, border stability, environmental security, and Uzbekistan’s geopolitical relevance in the region. Conclusions: Uzbekistan's strategic initiatives have significantly contributed to regional peace and stability while reinforcing economic and environmental cooperation. However, challenges such as Afghan instability, climate change, and water disputes remain critical to long-term regional security. Limitations: This study is based on secondary sources and public policy documents; it does not incorporate fieldwork or interviews with stakeholders in the region, which could enrich the understanding of local-level impacts. Contribution: This research contributes to regional studies and international relations by highlighting how a mid-sized state like Uzbekistan can play a catalytic role in fostering multilateral cooperation and addressing transboundary challenges in a post-Soviet context